α-MoO3 obtido pelo método Pechini modificado para aplicação como catalisador nas reações de transesterificação e esterificação - Sousa, Amanda Soares de (2023)
Molybdenum trioxide is a transition metal oxide, which has been extensively studied due to its various applications, especially in the area of heterogeneous catalysis, due to the diversity of acidic and basic sites that can be attributed to the functionalities present in its structure. In this work, this oxide was synthesized by the modified Pechini method and used as a heterogeneous catalyst in soybean oil methyl transesterification reactions, oleic acid methyl esterification reactions, as well as in both simultaneous reactions for biodiesel production. This oxide was obtained at 500 °C and characterized by X-ray Diffraction (XRD), Infrared Spectroscopy (IR), Raman Spectroscopy, UV-Visible Spectroscopy (UV-VIS), Surface Area Measurement (SBET), Zero Charge Point and Scanning Electron Microscopy (SEM). The diffractograms confirmed the obtaining of the orthorhombic phase, as indicated in the ICDD 005-0508 chart. The IR and Raman spectra confirmed the presence of the different Mo-O bonds present in the material. The micrographs showed morphologies in the form of lamellar plates, corroborating the structural organization and the surface area obtained for this catalyst was 0.501 m2g-1. The catalytic tests were performed in an autoclave reactor and parameters such as methanol:fatty matter molar ratio (12:1), 3% m/m of the catalyst, temperature and time variation were used for the transesterification and esterification reactions. The reduction of kinematic viscosity and acidity index of soybean oil and oleic acid for all tests using α-MoO3 as catalyst, indicated that transesterification and esterification processes occurred, respectively. In addition, by gas chromatography (GC) and 1H NMR techniques, in both reactions the highest conversion to methyl esters occurred using a temperature of 150 °C and a reaction time of 120 minutes, obtaining for the transesterification reaction (99.3 %) and for esterification (97.2%). With these same parameters, the transesterification and simultaneous esterification reaction (TES) was carried out using an acidified oil, the maximum conversion to methyl esters observed was 85.2%, confirming the catalytic potential and versatility of this oxide in the production of biodiesel.